N-type semiconductor sintered compact, electrical / electronic component, thermoelectric power generation device, and method for manufacturing n-type semiconductor sintered compact

By partially replacing manganese in high manganese silicides with elements from Groups 5 to 10, the n-type semiconductor sintered body achieves superior thermoelectric properties, addressing the limitations of existing n-type materials and improving the reliability of thermoelectric power generation devices.

JP2025063339AInactive Publication Date: 2025-04-16NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2022035415
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-03-08
Publication Date
2025-04-16
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing n-type semiconductor materials based on high manganese silicides suffer from inferior thermoelectric properties due to limited electrical conductivity and significant differences in thermal expansion coefficients when combined with p-type semiconductor materials.

Method used

Development of an n-type semiconductor sintered body with high manganese silicides partially replaced by elements from Groups 5 to 10, achieving electrical conductivity of 10,000 S/m or more and maintaining a chimney ladder crystal structure, thereby enhancing thermoelectric performance.

Benefits of technology

The approach results in n-type semiconductor materials with improved thermoelectric properties, including higher electrical conductivity and lower thermal conductivity, leading to enhanced thermoelectric figure of merit (ZT) and reliability in thermoelectric power generation devices.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

To provide n-type semiconductor materials containing high manganese silicide with excellent thermoelectric properties.SOLUTION: An n-type semiconductor sintered compact contains a polycrystalline material containing high manganese silicide partially substituted with one or more elements other than Mn of Groups 5 to 10, with an electrical conductivity of 10,000 S / m or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an n-type semiconductor sintered body, an electric / electronic member, a thermoelectric power generation device, and a method for producing an n-type semiconductor sintered body. [Background technology]

[0002] Some semiconductors are known to have a large electromotive force per temperature difference (Seebeck coefficient), and such semiconductors are known to be useful as thermoelectric materials for thermoelectric power generation. In particular, silicon-based alloy materials have been attracting attention in recent years due to their low toxicity, availability at low cost, and ease of control of their electrical properties.

[0003] In order for a thermoelectric material to have high thermoelectric performance, it is necessary for the material to have high electrical conductivity and low thermal conductivity. Although elemental silicon has a large Seebeck coefficient and high electrical conductivity, it often has low thermoelectric performance due to its high thermal conductivity. For this reason, various improvements to silicon have been made, and the use of silicon alloys made by adding other elements to silicon is also being considered. Among such silicon alloys, higher manganese silicides (HMS) are expected to be put to practical use because they provide relatively high power generation performance, are low in toxicity, and are inexpensive. (For example, Patent Document 1, Non-Patent Document 1)

[0004] Most high manganese silicides function as p-type semiconductors. Attempts have been made to convert high manganese silicides to n-type by partially replacing manganese in the high manganese silicides, and it is possible to convert them to n-type. However, since the amount of solid solution of the element added for the substitution in high manganese silicide is small, sufficient electrical conductivity cannot be obtained, and only n-type semiconductors with inferior thermoelectric properties have been obtained (for example, Non-Patent Document 3). Therefore, when combining p-type semiconductor power generating materials and n-type semiconductor power generating materials to configure a power generating device (power generating module), attempts have been made to use a different type of n-type power generating material (an n-type power generating material whose base material type is different from that of the p-type power generating material), for example, an alloy such as magnesium silicide, as a partner to be combined with p-type high manganese silicide (for example, Non-Patent Document 2). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 4849970 [Non-patent literature]

[0006] [Non-Patent Document 1] Miyazaki,Jpn. J. Appl. Phys.,2020,59,SF0802. [Non-Patent Document 2] Aoyama et al, Jpn. J. Appl. Phys.,2005,44,pp.4275-4281. [Non-Patent Document 3] Miyazaki et al,2011,Jpn. J. Appl. Phys.50,035804. Summary of the Invention [Problem to be solved by the invention]

[0007] However, when a power generating couple is formed from a p-type semiconductor power generating material and an n-type semiconductor power generating material by combining a manganese-based material and a magnesium-based material as described in Non-Patent Document 2, there is a problem of reduced reliability due to the difference in thermal expansion coefficient between the two materials. Therefore, there is a demand for a material containing an n-type higher manganese silicide that has higher thermoelectric properties.

[0008] In view of the above, an object of the present invention is to provide an n-type semiconductor material containing a higher manganese silicide, which has excellent thermoelectric properties. [Means for solving the problem]

[0009] One aspect of the present invention is an n-type semiconductor sintered body that includes a polycrystalline body containing a higher manganese silicide partially substituted with one or more elements of Groups 5 to 10 other than Mn, and has an electrical conductivity of 10,000 S / m or more. Effect of the Invention

[0010] According to one aspect of the present invention, it is possible to provide an n-type semiconductor material containing a higher manganese silicide, which has excellent thermoelectric properties. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, the embodiments of the present invention will be described in more detail. However, the present invention is not limited to the embodiments described herein, and appropriate combinations and improvements can be made without departing from the technical spirit of the invention.

[0012] (High manganese silicide) One aspect of the present invention is an n-type semiconductor sintered body that includes a polycrystalline body containing a higher manganese silicide partially substituted with one or more elements other than Mn of Groups 5 to 10 and exhibits high electrical conductivity. This aspect makes it possible to obtain an n-type higher manganese silicide thermoelectric material that exhibits high thermoelectric performance.

[0013] When evaluating the thermoelectric performance (also called thermoelectric conversion performance) of a thermoelectric material, the dimensionless thermoelectric figure of merit ZT[-] is often used. ZT can be calculated using the following formula: ZT = α 2 σT / κ (1) In formula (1), α [V / K] is the Seebeck coefficient, σ [S / m] is the electrical conductivity (in the unit "S / m", "S" is Siemens and "m" is meters), κ [W / (mK)] is the thermal conductivity, and T is the absolute temperature [K]. The Seebeck coefficient α refers to the potential difference generated per unit temperature difference. In addition, the larger the thermoelectric figure of merit ZT, the better the thermoelectric conversion performance. As is clear from formula (1), in order to improve the thermoelectric conversion performance ZT, it is desirable for the Seebeck coefficient α and electrical conductivity σ to be large and for the thermal conductivity κ to be small.

[0014] Generally, compounds or compositions made of manganese and silicon are classified into several types of substances as shown in known phase diagrams. The manganese silicide described in this specification is one of them, MnSi γ (where 1.6<γ<2) and has a characteristic crystal structure, specifically a crystal structure called a chimney ladder. High manganese silicide exhibits relatively low thermal conductivity due to this characteristic crystal structure, making it preferable as a thermoelectric material. It is also known that the Seebeck coefficient α of high manganese silicide-based materials, i.e., high manganese silicide or alloy materials containing high manganese silicide, is relatively high. Manganese silicide is less toxic and available at low cost compared to materials such as Bi2Te3 and PbTe. Furthermore, high manganese silicide materials or materials containing alloys containing high manganese silicide have a lower power factor (the product of the square of the Seebeck coefficient and electrical conductivity, α in the above formula (1)) than silicon materials and silicide materials (silicon germanium materials, etc.). 2 Therefore, by using a semiconductor sintered body containing high manganese silicide or based on high manganese silicide as in the present embodiment, it is possible to provide an environmentally friendly thermoelectric conversion element (thermoelectric power generation element), and further a thermoelectric power generation device, at low cost.

[0015] (n-type semiconductor sintered body) The n-type semiconductor sintered body according to this embodiment may be a sintered body of partially substituted high manganese silicide. The partially substituted high manganese silicide mainly contains high manganese silicide or is based on high manganese silicide, and at least a part of the manganese in the manganese silicide is substituted with a predetermined element. The n-type semiconductor sintered body according to this embodiment maintains the above-mentioned chimney ladder structure even in a partially substituted state.

[0016] Partially substituted manganese silicides have the formula (Mn (1-x) A x )(Si (1-y) B y ) γ In the formula, A is an element that replaces Mn in manganese silicide, and may be one or more elements other than Mn from group 5 to group 10. More specifically, A is preferably one or more elements selected from the group consisting of V, Nb, Ta, Cr, Mo, W, Re, Fe, Ru, Os, Co, Rh, Ir, and Ni. Furthermore, since it can promote the n-type of the semiconductor sintered body, A is more preferably an element shown to the right of Mn in the periodic table, that is, one or more elements from group 8 to group 10, and further preferably contains Co and / or Fe, or Co and / or Fe. Furthermore, if A contains Fe, it is more preferable because it can increase the Seebeck coefficient, is inexpensive, and is highly safe for the environment. The value of x in the above formula, i.e., the ratio of Mn substituted with A, can be 0 or more, preferably 0.28 or more, and more preferably 0.32 or more. Furthermore, due to the limit of the amount of solid solution in high manganese silicide, x may be 0.42 or less.

[0017] Furthermore, in the high manganese silicide of this embodiment, silicon may not be substituted, but a part of silicon may be substituted with another element. That is, in the above composition formula, the value of y, which represents the ratio of silicon substituted with B, may be 0 or may exceed 0. In addition, the value of y is preferably 20 or less. B is preferably one or more group 14 elements, and more preferably one or more elements selected from the group consisting of Ge and Sn. As described above, the atomic ratio γ of Si to Mn in the high manganese silicide is 1.6<γ<2, but in the n-type semiconductor sintered body according to this embodiment, i.e., in the partially substituted high manganese silicide, it may be 1.6<γ<2, and preferably 1.7<γ<1.8.

[0018] The n-type semiconductor sintered body according to this embodiment may be a high manganese silicide-based polycrystalline body, i.e., a polycrystalline body containing high manganese silicide as the main crystal. The main crystal refers to the crystal with the largest precipitation ratio in the XRD pattern, etc., and preferably refers to the crystal occupying 55 mass% or more of the entire polycrystalline body. The n-type semiconductor sintered body may contain manganese silicide (a heterogeneous compound containing manganese and silicide) other than high manganese silicide, such as manganese monosilicide.

[0019] In addition, the n-type semiconductor sintered body according to this embodiment may contain, in addition to the high manganese silicide partially substituted with a predetermined element, an alloy (including a solid solution, a eutectic, or an intermetallic compound) of the high manganese silicide and an element other than the above-mentioned predetermined element. Furthermore, the n-type semiconductor sintered body may contain an unsubstituted high manganese silicide, or may contain a polycrystalline body containing an element other than manganese and silicide.

[0020] The polycrystalline body (semiconductor sintered body) according to this embodiment can be obtained by melting a compound and / or a mixture thereof containing raw material elements at a temperature equal to or higher than the melting point and then cooling it, or by heating it to a high temperature under pressure at which it does not melt, thereby causing a solid-phase diffusion reaction. In the former method, an arc melting or high-frequency melting device can be used, and in the latter method, an inert atmosphere furnace, a spark plasma sintering machine, a hot press machine, a hot isostatic pressing (HIP) machine, or the like can be suitably used.

[0021] The electrical conductivity of the n-type semiconductor sintered body according to the present embodiment may be 10,000 S / m or more at 27°C, preferably 15,000 S / m or more, more preferably 20,000 S / m or more. In this way, the improved electrical conductivity can improve the thermoelectric performance. The upper limit of the electrical conductivity of the semiconductor sintered body may be 1,000,000 S / m or less at 27°C, or 500,000 S / m or less. The thermoelectric figure of merit ZT of the semiconductor sintered body according to the present embodiment can be, for example, 0.3 or more at 527°C, preferably 0.4 or more, and further 1.5 or more.

[0022] The thermal conductivity of the n-type semiconductor sintered body according to this embodiment is preferably 8 W / m K at 27° C., more preferably 5 W / m K or less, and may be 2 W / m K or less. The Seebeck coefficient of the semiconductor sintered body is preferably −300 to −50 μV / K at 27° C., and more preferably −300 to −100 μV / K.

[0023] In addition, the semiconductor sintered body according to this embodiment has an average grain size of 100 μm or less, more preferably 50 μm or less, and even more preferably 10 μm or less, whichever is more preferable. By setting the grain size of the crystal grains within the above range, it is expected that the thermal conductivity will be reduced, thereby improving the ZT value, and that the mechanical strength of the sintered body will be improved. In addition, the lower limit of the average grain size of the crystal grains is not particularly limited unless there are manufacturing constraints. If there are no constraints, it may be 1 nm or less, but it can be 1 nm or more.

[0024] In this specification, the average grain size of crystal grains refers to the median value of the longest diameter of each crystal grain constituting the crystal, measured by direct observation using a microscope such as a scanning electron microscope (SEM) or a transmission electron microscope (TEM).

[0025] (Dopant) The semiconductor sintered body according to the present embodiment may further contain an n-type dopant. By containing an n-type dopant, the concentration of carriers (free electrons) can be increased and the electrical conductivity can be improved, thereby improving the thermoelectric performance.

[0026] The n-type dopant can be appropriately selected depending on the configuration and application of the thermoelectric material to be obtained. The dopant is preferably uniformly dispersed throughout the sintered body. As the n-type dopant, it is preferable to use one of phosphorus, arsenic, and antimony alone or in combination of two or more. In addition, it is preferable that the n-type dopant is diffused into the partially substituted higher manganese silicide by diffusion doping, which will be described later.

[0027] The concentration of the n-type dopant in the sintered body (1 cm 3 The number of n-type dopant atoms per unit area is 0.1 to 10 × 10 20 atoms / cm 3 It is preferable that the dopant concentration is increased. Although the thermoelectric performance ZT is improved because the electrical conductivity can be improved by increasing the dopant concentration, if the dopant concentration is excessively large, the Seebeck coefficient decreases and the thermal conductivity increases, resulting in a decrease in the thermoelectric performance ZT. However, by setting the dopant concentration within the above range, the thermoelectric performance ZT can be improved. In this embodiment, the dopant concentration is equivalent to the carrier concentration calculated from the electrical characteristics.

[0028] (Application) As described above, according to this embodiment, a semiconductor sintered body having high electrical conductivity while maintaining low thermal conductivity can be obtained. Therefore, the n-type semiconductor sintered body according to this embodiment can be used as an electric / electronic member (i.e., an electric member and / or an electronic member), for example, a power generating material or a thermoelectric element. In particular, it can be suitably used in a power generating device that utilizes exhaust heat, for example, a power generating device mounted on the engine and exhaust system of an automobile or a ship, a power generating device mounted on the heat dissipation system of an industrially used heating furnace, and the like.

[0029] Furthermore, this embodiment may be a thermoelectric power generation device including the above-mentioned n-type semiconductor sintered body as an n-type thermoelectric element, and a p-type semiconductor sintered body including a partially substituted or unsubstituted high manganese silicide as a p-type thermoelectric element. When a p-type semiconductor sintered body including a partially substituted high manganese silicide is used as a p-type thermoelectric element, the element introduced in place of Mn may be one or more elements other than Mn in groups 5 to 10, and preferably one or more elements among elements in groups 5 and 6. In addition, the p-type semiconductor sintered body may be doped using diffusion doping described later. In that case, a dopant of an element other than an element in groups 5 to 10 may be used as the dopant. Furthermore, silicon of the high manganese silicide in the p-type semiconductor sintered body may be substituted with another element.

[0030] In a thermoelectric power generation device, it is preferable that the configurations (crystal grain size, content of higher manganese silicide, etc.) of an n-type semiconductor sintered body used as an n-type thermoelectric element and a p-type semiconductor sintered body used as a p-type thermoelectric element are the same or similar.

[0031] Thus, according to this embodiment, it is possible to provide a pair of semiconductor materials in which the same type of manganese silicide alloy substrate (material with high manganese silicide as the base material) is adjusted to have p-type and n-type characteristics. By using a high manganese silicide substrate for both the p-type thermoelectric element and the n-type thermoelectric element, the difference in thermal expansion coefficient between the two can be reduced, and therefore resistance to thermal stress breakdown is reduced. In addition, since both manganese and silicon are relatively inexpensive materials, it is economically preferable if both the p-type and n-type elements can be constructed using high manganese silicide.

[0032] (Method of manufacturing semiconductor sintered body) High manganese silicide is originally a p-type semiconductor. One way to make this unsubstituted high manganese silicide n-type is to partially but relatively largely replace Mn with an element shown to the right of Mn in the periodic table. This increases the carriers (free electrons) and allows an n-type semiconductor to be obtained. However, when such partial replacement is performed by solid solution (melting Mn and an element shown to the right of Mn in the periodic table together and crystallizing), there is a limit to the amount of the replaced element that can be dissolved in the high manganese silicide, and many elements cannot be introduced. For example, when Mn in high manganese silicide is partially replaced by Fe by solid solution, Fe can only be replaced up to about 0.35 of the original Mn atoms, and it is not possible to obtain a semiconductor with a higher carrier (free electron) concentration than this.

[0033] In contrast, the method for producing a semiconductor sintered body according to the present embodiment includes a particle preparation step of preparing particles containing high manganese silicide partially substituted with one or more elements other than Mn of Groups 5 to 10 and having an average particle size of 100 μm or less, a film formation step of forming a film containing a dopant element on the surface of the particles, and a sintering step of sintering the particles on which the film is formed to obtain a semiconductor sintered body. By the method according to the present embodiment, the dopant element diffuses from the film to the particles, and the dopant element can be diffused more uniformly and at a higher concentration. In this specification, the doping method according to the present embodiment may be called diffusion doping or thermal diffusion doping.

[0034] The particle preparation step includes melting a mixture of raw material elements, a compound containing raw material elements, or a mixture thereof at a temperature above the melting point and then cooling, or heating to a high temperature under pressure at which the mixture does not melt, thereby causing a solid-phase diffusion reaction to obtain a solid. In the former method, an arc melting or high-frequency melting device can be used, and in the latter method, an inert atmosphere furnace, a spark plasma sintering machine, a hot press machine, a hot isostatic pressing (HIP) machine, or the like can be suitably used. The latter method is preferred in that a uniform composition can be obtained.

[0035] The particle preparation step further includes preparing particles (powder) by pulverizing the obtained solid by a known pulverization method. Alternatively, the particles (powder) may be synthesized from a raw material of an alloy containing manganese and silicon by using a known crystal growth method such as chemical vapor deposition (CVD).

[0036] The average particle size of the particles prepared in the particle preparation step may be 100 μm or less, preferably less than 50 μm, and more preferably 1 μm. The D90 of the particles is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 10 μm or less. By setting the particle size of the particles before sintering to the above range, a sintered body having crystal grains with a particle size of 100 μm or less and being appropriately densified can be obtained. The lower limit of the average particle size of the particles prepared in the particle preparation step is not limited, but it is preferably 50 nm or more due to manufacturing constraints. In this specification, the average particle size of the particles can be the volume-based median diameter measured by a laser diffraction particle size distribution measuring device.

[0037] Subsequently, a film-forming step is performed to form a film containing a dopant element on the surface of the particles obtained in the particle preparation step. This film-forming step can be performed by dispersing the particles obtained in the particle preparation step in a solvent, adding a substance containing the dopant element, and mixing with a bead mill or the like. Thereafter, the solvent is removed by reducing pressure or the like, and the particles are dried to obtain a film containing a dopant element formed on the surface. In this case, the thickness of the film may be 0.5 to 5 nm. The film can also be formed by a method in which organic molecules are diffused using a gas constituting the atmosphere in which the particles exist as a single element without using a solvent.

[0038] The dopant element contained in the coating is not particularly limited as long as it is an n-type dopant element, and may be one or more of phosphorus, arsenic, and antimony.

[0039] The substance containing the dopant element may be a simple substance or a compound of the dopant element. It may also be a mixture of two or more simple substances, a mixture of two or more compounds, or a mixture of one or more simple substances and one or more compounds. When the substance containing the dopant element is a compound, the substance may be an organic compound or an inorganic compound. It may also be a polymer or a low molecular weight substance. The organic compound may be a hydride, an oxide, an oxo acid, or the like containing the dopant element. When the substance is a mixture, it may be a mixture of an organic compound containing a dopant element and an organic compound not containing a dopant element, or a mixture of an inorganic compound containing a dopant element and an organic compound containing a dopant element. When the substance containing a dopant element is a molecular substance, the coating formed in the coating formation step is preferably a monomolecular film.

[0040] When phosphorus is used as the n-type dopant element, phosphoric acid, alkylphosphonic acid, alkylphosphinic acid and its ester, polyvinylphosphonic acid, phosphine, trialkylphosphine such as triethylphosphine and tributylphosphine, etc. can be used. When arsenic is used as the dopant element, arsine, etc. can be used, when antimony is used, antimony trioxide, etc. can be used, and when bismuth is used, bismuthic acid can be used. The above substances may be used alone or in combination of two or more.

[0041] In the coating step, the substance containing the dopant element is preferably added in an amount of 3 to 80 parts by mass, more preferably 10 to 60 parts by mass, per 100 parts by mass of the particles prepared in the particle preparation step. By setting the amount in the above range, the electrical conductivity is increased and the thermal conductivity is suppressed, so that a semiconductor sintered body having high thermoelectric performance can be obtained.

[0042] The sintering step is not particularly limited as long as it is a method capable of sintering the above-mentioned raw material particles (powders), and examples thereof include spark plasma sintering (SPS), two-step sintering, hot pressing, hot isostatic pressing (HIP), microwave sintering, etc. Among these, it is preferable to use the spark plasma sintering method, which can obtain smaller crystal grains.

[0043] The sintering temperature in the sintering step can be selected according to the particle size and the composition of the partially substituted high manganese silicide, but is preferably 500° C. or higher, and more preferably 600° C. or higher. The sintering temperature is preferably 1100° C. or lower, and more preferably 1000° C. or lower. By setting the temperature within the above range, the densification of the sintered body can be promoted, and the average grain size of the crystal grains of the polycrystalline body can be maintained at 100 μm or less.

[0044] The heating rate in the sintering step is preferably 10 to 100° C. / min, and more preferably 20 to 60° C. / min. By setting the heating rate within the above range, uniform sintering can be promoted and excessively rapid grain growth can be suppressed, thereby maintaining the average grain size of the polycrystalline body at 100 μm or less.

[0045] In the sintering step, it is preferable to apply pressure, in which case the pressure is preferably 10 to 120 MPa, and more preferably 20 to 100 MPa.

[0046] As described above, when particles having a coating containing a dopant element formed on the surface are sintered (fired), the doping element is thermally diffused from the particle interface into the inside of the particle during sintering. The electrical conductivity of the resulting sintered body can be improved by such doping by thermal diffusion from the particle interface (diffusion doping). According to the method of this embodiment, the carrier can be doped at a higher concentration than doping performed without using thermal diffusion. Furthermore, the semiconductor sintered body obtained by the method of this embodiment can exhibit a higher electrical conductivity even when compared with a sintered body having the same dopant concentration but doped without using thermal diffusion from the particle interface.

[0047] In addition, one embodiment of the present invention is an n-type semiconductor sintered body produced by preparing particles containing high manganese silicide partially substituted with one or more elements other than Mn of Groups 5 to 10, forming a coating containing a dopant on the surface of the particles, and sintering the particles on which the coating is formed to obtain an n-type semiconductor sintered body. The n-type semiconductor sintered body according to this embodiment maintains the chimney ladder structure of high manganese silicide and contains carriers (free electrons) at a higher concentration. Therefore, it has low thermal conductivity and also high electrical conductivity. Therefore, it is possible to provide an n-type semiconductor sintered body having high thermoelectric performance ZT and made of high manganese silicide as a base material.

[0048] As described above, in the method according to the present embodiment, a coating containing a dopant element is formed on the surface of the particle in the coating step, and the dopant element in the coating is thermally diffused from the particle surface into the inside of the particle in the sintering step, thereby performing doping. However, the above-mentioned dopant element may be contained in the particle in advance in the particle preparation step, and then the above-mentioned coating step may be performed. For example, in the step of melting an alloy material containing manganese, silicon, and one or more elements other than Mn of groups 5 to 10 that will become the main crystal, a substance containing a dopant element is mixed, and the obtained molten material is cooled and pulverized, thereby preparing particles (powder) containing a dopant. Alternatively, a mixture of a powder of an alloy containing one or more elements other than manganese, silicon, and one or more elements other than Mn of groups 5 to 10 and a powder of a substance containing a dopant element is obtained, and the mixture is subjected to a solid-phase diffusion reaction at a high temperature under pressure at a level that does not melt the mixture, thereby preparing a mass obtained by pulverizing the mass. Furthermore, when preparing particles using chemical vapor deposition (CVD) or the like, the raw material for obtaining the partially substituted higher manganese silicide and a substance containing a dopant element can be mixed in a gas phase and condensed to prepare the above-mentioned particles containing the dopant element.

[0049] In this way, dopants (phosphorus, arsenic, antimony, etc.) are incorporated into the particles during the particle preparation step, and the dopants are further thermally diffused from the coating through the coating formation step and firing step, making it possible to achieve higher concentration doping. EXAMPLES

[0050] <Example 1> (Preparation of manganese silicide particles) 4.3 g of manganese (purity 99.99% or more), 5.6 g of silicon (purity 99.99% or more), and 2.3 g of iron (purity 99.99% or more) were placed in a graphite die / punch tool, and pressure and heat treatment was performed for 10 minutes under conditions of 50 MPa and 800°C in an argon atmosphere using a spark plasma sintering device, and then cooled. The resulting mass was crushed to 63 μm or less using a hammer crusher and a planetary ball mill. This was sieved to obtain particles of high manganese silicide-iron alloy.

[0051] (Particle Coating) The obtained high manganese silicide-iron alloy particles were dispersed in heptane, and a mixture of 5.0 g of high manganese silicide-iron alloy particles and 0.4 g of polyvinylphosphonic acid (Sigma-Aldrich, No. 661740) was added to the planetary ball mill and mixed for 300 minutes. After that, the heptane was removed under reduced pressure, and the mixture was dried to obtain high manganese silicide-iron alloy particles covered with a monolayer (high manganese silicide particles partially substituted with Fe).

[0052] (Sintering) The monolayer-coated high manganese silicide-iron alloy particles were placed in a graphite die / punch tool and heated to 800°C using a spark plasma sintering device to obtain a sintered body. The applied pressure was 40 MPa and the heating rate was 50°C / min. The outer surface of the obtained sintered body was roughly polished to remove the impurity layer derived from graphite, etc. The sintered body was then cut using a dicing saw to obtain rectangular parallelepiped chips.

[0053] (Structure and Characteristics) The density of the sintered body measured by Archimedes method was 98.5% of that of pure manganese silicide-iron alloy. The electrical conductivity of the sintered body at 27°C was 2.1×10 4 The thermal conductivity was 3.0 W / m K and the Seebeck coefficient of the sintered body was -115.5 μV / K. The carrier concentration was calculated based on the Seebeck coefficient of the sintered body (-115.5 μV / K). 20 Atoms / cm 3The thermoelectric figure of merit ZT at 527°C was 0.23.

[0054] <Example 2> (Preparation of manganese silicide particles) In the same manner as in Example 1, high manganese silicide-iron alloy particles were obtained.

[0055] (Particle Coating) The obtained high manganese silicide-iron alloy particles were dispersed in heptane, and a mixture of 5.0 g of high manganese silicide-iron alloy particles and 1.0 g of polyvinylphosphonic acid (Sigma-Aldrich, No. 661740) was added and placed in the planetary ball mill and mixed for 300 minutes. After that, the heptane was removed under reduced pressure, and the mixture was dried to obtain high manganese silicide-iron alloy particles covered with a monolayer (high manganese silicide particles partially substituted with Fe).

[0056] (Sintering) The monolayer-coated high manganese silicide-iron alloy particles were placed in a graphite die / punch tool and heated to 800°C using a spark plasma sintering device to obtain a sintered body. The applied pressure was 40 MPa and the heating rate was 50°C / min. The outer surface of the obtained sintered body was roughly polished to remove the impurity layer derived from graphite, etc. The sintered body was then cut using a dicing saw to obtain rectangular parallelepiped chips.

[0057] (Structure and Characteristics) The density of the sintered body measured by Archimedes method was 98.2% of that of pure manganese silicide-iron alloy. The electrical conductivity of the sintered body at 27°C was 3.7×10 4 The thermal conductivity was 3.3 W / m K. The carrier concentration was calculated based on the Seebeck coefficient of the sintered body (-95.5 μV / K), and was [10 20 atoms / cm 3 The thermoelectric figure of merit ZT at 527°C was 0.30.

[0058] <Example 3> (Preparation of manganese silicide particles) In the same manner as in Example 1, high manganese silicide-iron alloy particles were obtained.

[0059] (Particle Coating) The obtained high manganese silicide-iron alloy particles were dispersed in heptane, and a mixture of 5.0 g of high manganese silicide-iron alloy particles and 2.0 g of polyvinylphosphonic acid (Sigma-Aldrich, No. 661740) was added to the planetary ball mill and mixed for 300 minutes. After that, the heptane was removed under reduced pressure, and the mixture was dried to obtain high manganese silicide-iron alloy particles covered with a monolayer (high manganese silicide particles partially substituted with Fe).

[0060] (Sintering) The monolayer-coated high manganese silicide-iron alloy particles were placed in a graphite die / punch tool and heated to 800°C using a spark plasma sintering device to obtain a sintered body. The applied pressure was 40 MPa and the heating rate was 50°C / min. The outer surface of the obtained sintered body was roughly polished to remove the impurity layer derived from graphite, etc. The sintered body was then cut using a dicing saw to obtain rectangular parallelepiped chips.

[0061] (Structure and Characteristics) The density of the sintered body measured by Archimedes method was 98.7% of that of pure manganese silicide-iron alloy. The electrical conductivity of the sintered body at 27°C was 4.1×10 4 The thermal conductivity was 3.5 W / m K and the Seebeck coefficient of the sintered body was -79.4 μV / K. The carrier concentration was calculated based on the Seebeck coefficient of the sintered body (-79.4 μV / K). 20 Atoms / cm 3 The thermoelectric figure of merit ZT at 527°C was 0.32.

[0062] <Example 4> (Preparation of manganese silicide particles) 4.3g of manganese (purity 99.99% or more), 5.6g of silicon (purity 99.99% or more), 0.18g of germanium (purity 99.99% or more), and 2.3g of iron (purity 99.99% or more) were placed in a graphite die / punch tool, and pressure and heat treatment was performed for 10 minutes under conditions of 50 MPa and 800°C in an argon atmosphere using a spark plasma sintering device, and then cooled. The resulting mass was crushed to 63 μm or less using a hammer crusher and a planetary ball mill. This was sieved to obtain particles of high manganese silicide germicide-iron alloy.

[0063] (Particle Coating) The obtained high manganese silicide germicide-iron alloy particles were dispersed in heptane, and a mixture of 5.0 g of high manganese silicide-iron alloy particles and 1 g of polyvinyl phosphonic acid (Sigma-Aldrich, No. 661740) was added to the planetary ball mill and mixed for 300 minutes. After that, the heptane was removed under reduced pressure, and the mixture was dried to obtain high manganese silicide germicide-iron alloy particles covered with a monolayer (high manganese silicide germicide particles partially substituted with Fe).

[0064] (Sintering) The monolayer-coated high manganese silicide gelmicide-iron alloy particles were placed in a graphite die / punch tool and heated to 800°C using a spark plasma sintering device to obtain a sintered body. The applied pressure was 40 MPa and the heating rate was 50°C / min. The outer surface of the obtained sintered body was roughly polished to remove the impurity layer derived from graphite, etc. The sintered body was then cut using a dicing saw to obtain rectangular parallelepiped chips.

[0065] (Structure and Characteristics) The density of the sintered body measured by Archimedes method was 97.8% of that of pure manganese silicide germicide-iron alloy. The electrical conductivity of the sintered body at 27°C was 3.8×10 4 The thermal conductivity was 3.2 W / m K. The carrier concentration was calculated based on the Seebeck coefficient of the sintered body (-83.1 μV / K), and was found to be [1020 Atoms / cm 3 The thermoelectric figure of merit ZT at 527°C was 0.39.

[0066] <Comparative Example 1> High manganese silicide-iron alloy particles were obtained and sintered in the same manner as in Example 1, except that the particles were not coated.

[0067] The density of the sintered body measured by Archimedes method was 98.5% of that of pure manganese silicide-iron alloy. The electrical conductivity of the sintered body at 27°C was 0.79×10 4 The thermal conductivity was 3.3 W / m K and the Seebeck coefficient of the sintered body was -112.1 μV / K. The carrier concentration was calculated based on the Seebeck coefficient of the sintered body (-112.1 μV / K). 20 Atoms / cm 3 The thermoelectric figure of merit ZT at 527°C was 0.13.

[0068] As described above, it was found that the electrical conductivity of Examples 1 to 4, in which high manganese silicide-iron alloy (high manganese silicide partially substituted with Fe) or high manganese germanium silicide-iron alloy (high manganese germanium silicide partially substituted with Fe) was subjected to diffusion doping with phosphorus as a dopant element, was higher than the electrical conductivity of Comparative Example 1, in which no diffusion doping was performed.

Claims

1. The polycrystalline body includes a high manganese silicide partially substituted with one or more elements other than Mn of Groups 5 to 10, An n-type semiconductor sintered body having an electrical conductivity of 10,000 S / m or more.

2. The n-type semiconductor sintered body according to claim 1 , containing one or more dopants selected from the group consisting of phosphorus, arsenic, and antimony.

3. Formula (Mn (1-x) A x ) (Si (1-y) B y ) γ [In the formula, A is one or more elements selected from the group consisting of Fe, Ru, Os, Co, Rh, and Ir, B is one or more elements selected from the group consisting of Ge and Sn, and 0 < x ≦ 0.42, 0 ≦ y < 20, 1.6 < γ < 2]. The n-type semiconductor sintered body according to claim 1 or 2, comprising a polycrystalline body represented by the formula:

4. The n-type semiconductor sintered body according to claim 3 , wherein in the formula, A is Fe.

5. The n-type semiconductor sintered body according to claim 3 or 4, wherein, in the formula, y = 0.

6. An electric or electronic component comprising the n-type semiconductor sintered body according to any one of claims 1 to 5.

7. The n-type semiconductor sintered body according to any one of claims 1 to 5 is provided as an n-type thermoelectric element, A thermoelectric power generation device comprising a p-type semiconductor sintered body including a polycrystalline body containing a substituted or unsubstituted higher manganese silicide as a p-type thermoelectric element.

8. A particle preparation step of preparing particles including a higher manganese silicide partially substituted with one or more elements other than Mn of Groups 5 to 10; a coating step of forming a coating containing a dopant on the surface of the particles; a sintering step of sintering the particles having the coating formed on the surface thereof to obtain an n-type semiconductor sintered body; A method for producing an n-type semiconductor sintered body, comprising:

9. The method for producing an n-type semiconductor sintered body according to claim 8 , wherein the dopant includes one or more selected from the group consisting of phosphorus, arsenic, and antimony.

10. The method for producing an n-type semiconductor sintered body according to claim 8 or 9, wherein the at least one element other than Mn which is an element of Groups 5 to 10 is Fe.

11. The method for producing an n-type semiconductor sintered body according to claim 8 , wherein the sintering step is carried out at a temperature of 600° C. or higher.

12. The method for producing an n-type semiconductor sintered body according to claim 8 , wherein the sintering step includes performing spark plasma sintering.

Citation Information

Patent Citations

  • JP1973049970A